Phrasal and clausal architecture : syntactic derivation and interpretation : in honor of Joseph E. Emonds - Karimi, Simin; Samiian, Vida; Wilkins, Wendy K.; Emonds, Joseph E. (Linguistik aktuell ;, 2007)
The present collection includes papers that address a wide range of syntactic phenomena. In some, the authors discuss such major syntactic properties as clausal architecture, syntactic labels and derivation, and the nature of features and their role with respect to movement, agreement, and event-related constructions. In addition, several papers offer syntax-based discussions of aspects of acquisition, pedagogy, and neurolinguistics, addressing issues related to case marking, negation, thematic relations, and more. Several papers report on new findings relevant to less commonly investigated la.